Optimizing Four-Wheeled Patrol of the Turjawali Samapta Unit to Prevent the Criminal Act of Theft by Weighting in the Jurisdiction of Pati Police District - Widiatmoko, Rahmat Hersa (Advances in Police Science Research Journal, 2024)
The globalization has affected to the economic sector. This condition makes people a lot of thinking to meet life’s needs with various ways. The inequality will be the main factor causing disturbances of security and order, such as theft by weighting. This is the full attention of Police Institution, especially for The Turjawali Samapta Unit in preventive efforts through four-wheeled patrol activities. However, patrols are still considered insufficient to solve the problem considering the crime rate has not decreased. Therefore, this study focuses on optimizing four-wheeled patrols to prevent the criminal acts of theft by weighting in the jurisdiction of The Pati Police District. This reaserch uses a qualitative approach with the type of field research and it’s located in the jurisdiction of the Pati Police District. Reasearches use a management and organizational resources theory with the concepts that are the focus of the problems such as optimization, prevention, and outlines. The results of the study provide information that the four-wheeled patrols that are being carried out are stil not optimal. This is caused by organizational resources, systems and mechanism that are not in accordance with the provisions and the less optimal efforts that have been made by the Turjawali Samapta Unit. Therefore, the crime of theft by weighting In the jurisdiction of the Pati Police in 2022 as of October has increased. So, the aim of this research is to find a solution to this problem. The author’s recommendation for solving the problem of fourwheeled patrol organization resources is through the Sharing for Caring (SFC) program and managaement of budget allocations on target. In addition, solving problems with the four-wheeled patrol system and mechanisme is in the form of optimizing the Pantau Pati application and carrying out routine cooperation and coordination between units to support solving problems related to theft by weighting.